Dann waren's nur noch vier ... Wie viele (und welche) Maßnahmen der aktiven Arbeitsmarktpolitik brauchen wir noch? Eine Bilanz nach der Evaluation der Hartz-Reformen - Werner Eichhorst; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2007)
With the Hartz reforms active labor market policies in Germany were overhauled considerably. The paper reviews the recent evaluation findings and draws some conclusion for the future setup of active labor market policies in Germany. It argues in favor of a streamlined repertoire of active labor market policy schemes focusing on programs with proven positive effects (wage subsidies, training, start-up grants and placement vouchers) and calls for a systematic evaluation of all schemes not scrutinized so far.
urn:nbn:de:101:1-20080422151
Keywords: 330; Arbeitsmarktpolitik; Hartz-Reform; Wirkungsanalyse; Deutschland